Peran Lingkungan dan Masyarakat dalam manajemen Pendidikan Islam - Maelani, Evi; Suklani (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
Fulfillment of national education standards as a barometer of institutional quality experiences obstacles that are sometimes very serious. However, there are also historical, cultural factors and many other components that also have an influence. This is where the ability to manage the potential that exists and grows in society is needed so that it becomes capital in managing educational institutions. Therefore, this research aims to determine community participation in the sustainability of educational institutions. To find out how the management of educational institutions manages the potential of the surrounding community in managing educational institutions, as well as to explore supporting elements and elements that hinder the process of community participation in educational institutions. The research pattern used here is literature review. The results obtained from this research are that methods that can be used in participation management patterns include, 1) Developing strong parent-child and community communication. 2) Involving Parents and the Community in School Programs and 3) providing invitations to the surrounding environment to the annual community school meeting.